Plan estratégico para el centro de atención ambulatoria IESS Santo Domingo, para el año 2015-2019, según lineamientos del plan nacional del buen vivir - Castellano Popayan, Rosa Magaly (2015)
This research project is done in the Ambulatory Care Center of the Ecuadorian Institute of Social Security of the province of Santo Domingo de los Tsáchilas. This institution is involved in the provision of medical services second tier, provides emergency services, Operating Room, Imaging, Clinical Laboratory, Outpatient, Pediatrics, Gynecology, Dentistry, Orthopedics, Pharmacy, Development and Promotion of Health Psychology. When you start this work was formulated as a general goal, develop a strategic plan for the Ambulatory Care Center Santo Domingo IESS for the year 2015-2019, according to the guidelines of the National Plan for Good Living., The research is to identify the main problems administrative and medical management, defining strategies to modify and adapt attitudes, habits and behavior patterns of all staff to the process of organizational and cultural change to take appropriate future needs to improve the quality of care for members and increase productivity. The current research was carried out in the city of Santo Domingo of the Tsachilas, the general objective is to develop a strategic plan for the IESS Ambulatory Health Center Santo Domingo for the year 2015-2019, according to the guidelines of the National Plan for the Good Living. This institution is immersed with the provision of second-level medical services, the research consists in defining appropriate strategies to improve the attention quality and care for members and increase productivity. The methodology focuses on the external analysis under which the company operates, in order to identify opportunities and threats. On the other hand, an internal analysis was performed to recognize the strengths and weaknesses of the entity, so afterwards present the SWOT analysis, in which were implemented strategies. In addition surveys were conducted to civil servants and affiliates, interview with the Managing Director, who provided information for the preparation of the Strategic Plan. The main problems were detected in the administration management and medical services that affect organizational development. The Strategic Plan will allow to fullfil with the actions and objectives of this institution in a long-term, according to the guidelines of the National Plan of Good Living; getting as result a better quality and integral health care and in this way achieving greater user satisfaction. Keywords: Planning, management, organization, strategies.